Hereditable variants of classical protein tyrosine phosphatase genes: Will they prove innocent or guilty? - Hendriks, Wiljan J. A. J.; van Cruchten, Remco T. P.; Pulido, Rafael (Frontiers in Cell and Developmental Biology, 2023)
Protein tyrosine phosphatases, together with protein tyrosine kinases, control many molecular signaling steps that control life at cellular and organismal levels. Impairing alterations in the genes encoding the involved proteins is expected to profoundly affect the quality of life – if compatible with life at all. Here, we review the current knowledge on the effects of germline variants that have been reported for genes encoding a subset of the protein tyrosine phosphatase superfamily; that of the thirty seven classical members. The conclusion must be that the newest genome research tools produced an avalanche of data that suggest ‘guilt by association’ for individual genes to specific disorders. Future research should face the challenge to investigate these accusations thoroughly and convincingly, to reach a mature genotype-phenotype map for this intriguing protein family.